Characterization of an in vitro model to study CD4+ T cell metabolism in dairy cows - U. Arshad; M. Cid de la Paz; H.M. White; L.R. Cangiano (JDS Communications)
Dairy cows are susceptible to several health disorders throughout their lactation. Objectives were to characterize an in vitro model to study bioenergetic measures in CD4+ T lymphocytes in dairy cows. Twenty-four healthy mid-lactation multiparous Holstein dairy cows were enrolled at a mean (±SD) of 234 ± 22 DIM. Cows were blocked according to DIM and blood was collected to isolate peripheral blood mononuclear cells followed by magnetic separation of CD4+ T lymphocytes using bovine-specific monoclonal antibodies. The isolated CD4+ T lymphocytes from each cow were split into 2 tubes and randomly assigned to incubate in an assay medium as control (CON) or with a combination of phorbol myristate acetate and ionomycin (PMA+IMY) to evaluate metabolic function under a resting and activated state. Mitochondrial and glycolytic functional kinetics were recorded in CD4+ T lymphocytes based on real-time measurement of oxygen consumption rate (OCR) and extracellular acidification rate (ECAR) under basal conditions and in response to complex V inhibitor (oligomycin), a protonophore uncoupler (BAM 15), and complex I and complex III inhibitors (rotenone and antimycin A). The mean (±SD) viability and purity of CD4+ T lymphocytes was 92.5 ± 2.9% and 95.2 ± 2.9%, respectively. The basal OCR in CD4+ T lymphocytes treated with PMA+IMY was greater than CON; nevertheless, the maximal respiration rate (CON = 58.0 vs. PMA+IMY = 47.3 ± 5.7 pmol/min) and sparing respiratory capacity rate (CON = 42.0 vs. PMA+IMY = 28.7 ± 4.2 pmol/min) were decreased in activated CD4+ T lymphocytes. The ECAR in CD4+ T lymphocytes increased progressively over time in PMA+IMY compared with CON, which indicated an increase in aerobic glycolysis in PMA+IMY compared with CON (CON = 46.9 vs. PMA+IMY = 86.4 ± 7.0 pmol/min). Activated CD4+ T lymphocytes exhibit a metabolic switch from oxidative phosphorylation to aerobic glycolysis, which may support rapid cell proliferation. The results observed in this experiment demonstrate the sensitivity of the technique to detect changes in metabolic function under different cellular conditions, providing a robust framework to study immuno-metabolism in dairy cattle.